Implementation of Background Subtraction and Fuzzy Logic Control for Green-Timing Optimization on 3-Junction Traffic Light - Dharmawan -; Rahmadwati Rahmadwati; Hadi Suyono (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
This study presents a green-timing optimization simulation on a 3-lane traffic light to reduce the density of the vehicle queue (density) in each lane. The method used in green-timing optimization is a combination of background subtraction and fuzzy logic control. Background subtraction functions as density extractor and fuzzy logic control as the green-timing controller itself. Green-timing optimization simulations in this study show a decrease in waiting time in each cycle of timing and a decrease in traffic-density of 44% -45% compared to a fixed-time timing system.Keywords: background substraction, fuzzy, green-timing, logic control, traffic light.